THE DEVELOPMENT OF TEACHING AND LEARNING (CTL)-BASED ECOSYSTEM MODULE FOR LEARNING BIOLOGY IN X-CLASS OF SENIOR HIGH SCHOOL - RAESITA MERRIA DEWI (Berkala Ilmiah Pendidikan Biologi (BioEdu), 2012)
ABSTRACT- The use of module in learning is important because it can be a means to increase the activity and creativity of students’s learning so that the students can get the best results during the learning process. The research of development of Contextual Teaching and Learning (CTL)-based ecosystem module is intended to describe feasibility of ecosystem module and describes student’s readibility dan responses to Contextual Teaching and Learning (CTL)-based ecosystem module. This research is the research of development of module using 4-D models. This models consists of 4 stages that is define, design, develop and desseminate. This research was carried out only up to the develop stage. The research was conducted in biology FMIPA UNESA and SMA Muhammadiyah 4 Surabaya on June 2011 until February 2012. The parameters measured is the study of experts that be analysized descriptively. Module is said to be feasible if the interpretation of the results of expert examination  ≥ 2,27. The results of the research suggest that Contextual Teaching and Learning (CTL)-based ecosystem module obtains a very feasible category for use in learning. It can be seen from the results of expert examination’s average score is 3,67 with the criteria is feasible. Keywords: module, ecosystems, Contextual Teaching and Learning (CTL)